2002
DOI: 10.1099/0022-1317-83-2-359
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A virus polyprotein processing by Escherichia coli proteases

Abstract: Hepatitis A virus (HAV) encodes a single polyprotein, which is post-translationally processed. This processing represents an essential step in capsid formation. The virus possesses only one protease, 3C, responsible for all cleavages, except for that at the VP1/2A junction region, which is processed by cellular proteases. In this study, data demonstrates that HAV polyprotein processing by Escherichia coli protease(s) leads to the formation of particulate structures. P3 polyprotein processing in E. coli is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…All MAbs were used at the highest dilution yielding recognition of the pHM175 43c strain of HAV. This strain, although resistant to neutralization by MAb K24F2 (26), still shows antibody binding (30) and is well recognized by ELISA at a high concentration of the antibody (31). Thus, the dilutions used were 1/10,000 for H7C27 and K34C8 MAbs and 1/250 for K24F2 MAb.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…All MAbs were used at the highest dilution yielding recognition of the pHM175 43c strain of HAV. This strain, although resistant to neutralization by MAb K24F2 (26), still shows antibody binding (30) and is well recognized by ELISA at a high concentration of the antibody (31). Thus, the dilutions used were 1/10,000 for H7C27 and K34C8 MAbs and 1/250 for K24F2 MAb.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…In this study, we demonstrated that a reporter cell line expressing fluorogenic protease substrate responds well to viral infection, and the infected cells could be detected easily through fluorescent microscopy. The reporter cells responded to all three enteroviruses tested with different sensitivities and did not respond to HAV, which is also a member of Picornaviridae, but it does not encode protease 2A (37). The reporter cells achieved the same detection limit for PV1 and EV11 (Յ10 PFU) but had a higher detection limit for CVB6 (Յ100 PFU) ( Table 1).…”
Section: Discussionmentioning
confidence: 90%
“…The morphogenesis pathway of the different populations was analyzed as previously described (24,25). Portions (500 l) of concentrated viral stocks were layered onto a 15 to 45% sucrose gradient in TNMg buffer (20 mM Tris-HCl, 10 mM NaCl, 50 mM MgCl 2 [pH 6.7]) and spun at 205,000 ϫ g for 165 min.…”
Section: Methodsmentioning
confidence: 99%